Superlithiophilic Amorphous SiO2–TiO2 Distributed into Porous Carbon Skeleton Enabling Uniform Lithium Deposition for Stable Lithium Metal Batteries. Issue 18 (22nd July 2019) - Xue, Pan; Sun, Chuang; Li, Hongpeng; Liang, Jiajie; Lai, Chao
Abstract: Lithium (Li) metal anodes have garnered increasing interest in recent years as its high theoretical capacity and low electrochemical potential promises a myriad of opportunities for various applications. However, one critical issue to overcome is the inhomogeneous deposition of Li + during the plating and stripping process. This inhomogeneous deposition could result in uncontrollable dendrite growth, further leading to poor coulombic efficiency, shorter lifecycles, and safety concerns due to internal short circuit and thermal runaways. To address these issues, a 3D porous core–shell fiber scaffold is presented, comprising of well‐dispersed SiO2, TiO2, and carbon, as superlithiophilic host materials for lithium anodes. The amorphous SiO2 and TiO2 allow for controllable nucleation and deposition of metal Li inside the porous core–shell fiber even at ultrahigh current densities of 10 mA cm −2 . In addition, the interconnected conductive fiber with high porosity enables good electrical conductivity with fast ion transport and excellent mechanical strength to withstand massive Li loading during repeated cycles of stripping and plating. As a result, excellent cycling performance and high rate capability are observed in both symmetric cells and full cells, highlighting the feasibility of the proposed Li anode composite. Abstract : Superlithiophilic 3D porous core–shell fiber scaffold, which contains well‐dispersed amorphous TiO2, SiO2, and conductive carbon, are successfully prepared via electrospinning, and investigated as host materials for metal lithium anodes. Amorphous TiO2 and SiO2 present high binding energy with Li atoms, and thus can effectively regulate the uniform deposition of Li.